Trajectories of Kinesiophobia and Influencing Factors in Patients With Acute Myocardial Infarction - Ying Wang; Jiawei Fan; Hongji Qian; Xiaoqing Shi (Clinical Nursing Research, 2026)
It is widely acknowledged that kinesiophobia is prevalent among patients suffering from acute myocardial infarction (AMI). Although heightened kinesiophobia significantly predicts adverse outcomes, it should be recognized that this fear is dynamic and typically evolves during the recovery process. This study aims to identify distinct trajectories of kinesiophobia and analyze associated influencing factors to accurately detect patients with high levels of kinesiophobia. AMI patients were enrolled from November 2023 to July 2024. Data on kinesiophobia, demographic and clinical characteristics, depression, exercise self-efficacy, and exercise social support were collected. Latent Class Growth Modeling was employed to identify distinct trajectories of kinesiophobia. Subsequently, multivariate logistic regression analysis was performed to identify predictors associated with different kinesiophobia trajectory categories. Initially, 239 patients were recruited, and after 4 follow-up assessments, 207 patients who completed at least 2 assessments were included in the analysis. The total scores of the Tampa Scale for Kinesiophobia-Heart generally demonstrated a decreasing trend ( p < .05). Three trajectories of kinesiophobia were identified: persistently high ( N = 49, 24.9% of the sample), persistently low ( N = 50, 24.5% of the sample), and high-to-critical ( N = 108, 50.6% of the sample). Predictive factors distinguishing the persistently high group from the persistently low group included exercise self-efficacy, age, gender, length of hospitalization, and the number of stents implanted. Predictors for the high-to-critical group included exercise self-efficacy, age, and the number of stents implanted. Kinesiophobia in AMI patients exhibited significant heterogeneity, with trajectories demonstrating relative stability over time. Consequently, individuals with high initial kinesiophobia levels often experienced limited alleviation during rehabilitation. Therefore, timely interventions to mitigate fear of movement are critical. Such interventions can reduce kinesiophobia to low levels during rehabilitation and improve patient prognosis.